Occupational and environmental health - Levy, Barry S.; Wegman, David H.; Baron, Sherry L.; Sokas, Rosemary K. (New York, NY : Oxford University Press, 2017)
This seventh edition is a comprehensive, practical guide to recognizing, preventing and treating work-related and environmentally-induced injuries and diseases. Numerous case studies, photographs, drawings, graphs and tables help readers understand key concepts.
This edition previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on October 17, 2017).
Keywords: Medicine, Industrial